2020
DOI: 10.3389/fimmu.2020.00179
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Plasticity of HLA-B27 Molecules Correlates Inversely With Efficiency of Negative T Cell Selection

Abstract: The development of autoimmune disorders is incompletely understood. Inefficient thymic T cell selection against self-peptides presented by major histocompatibility antigens (HLA in humans) may contribute to the emergence of auto-reactive effector cells, and molecular mimicry between foreign and self-peptides could promote T cell cross-reactivity. A pair of class I subtypes, HLA-B2705 and HLA-B2709, have previously been intensely studied, because they are distinguished from each other only by a single amino aci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…According to this theory, predisposing MHC-I molecules may exhibit properties which could cause excessive misfolding and accumulation in the ER, promoting the 'unfolded protein response'. [33][34][35][36][37][38] Studies of (HLA-B*27) transgenic animals and cellular models support this hypothesis, but there is a paucity of translational evidence. [39][40][41][42][43] A third popular hypothesis suggests that the predisposing MHC-I alleles are recognised by KIRs or leucocyte immunoglobulin-like receptors (LILRs) on the cell surface of NK cells.…”
Section: The Inception Of the Mhc-i-opathy Familymentioning
confidence: 99%
“…According to this theory, predisposing MHC-I molecules may exhibit properties which could cause excessive misfolding and accumulation in the ER, promoting the 'unfolded protein response'. [33][34][35][36][37][38] Studies of (HLA-B*27) transgenic animals and cellular models support this hypothesis, but there is a paucity of translational evidence. [39][40][41][42][43] A third popular hypothesis suggests that the predisposing MHC-I alleles are recognised by KIRs or leucocyte immunoglobulin-like receptors (LILRs) on the cell surface of NK cells.…”
Section: The Inception Of the Mhc-i-opathy Familymentioning
confidence: 99%
“…It has been suggested that molecular plasticity inversely correlates with the efficiency of negative T cell selection within the thymic medulla. This process may be impaired when the T cells confront a highly flexible binding groove, causing the failure of negative selection against self-peptide [ 17 , 18 ]. The surviving CD8 + T lymphocytes would then recognize these peptides in peripheral tissues, in contrast to what happens in the thymus, due to increased peptide concentration in key peripheral tissues or post-translationally modifications that take place in specific tissues [ 19 ].…”
Section: Hla-b27: the Main Genetic Player In Axial-spa Pathogenesismentioning
confidence: 99%
“…The nature of the peptidome efficiently bound and presented by HLA-B*27 is highly influenced by the stability of the molecule itself; several studies have described a higher flexibility of HLA-B*27:05, compared to B*27:09, suggesting an intrinsic propensity of this subtype to adopt unconventional conformations, especially in the proximity of the binding groove [ 44 , 45 , 46 ]. Moreover, a recent work by Loll’s research group has suggested that HLA-B*27:05, but not B*27:09, undergoes metal ion-induced conformational alterations that, in turn, could influence the capability of the AS-associated allele to bind suboptimal peptides [ 47 ].…”
Section: Hla-b*27 and Spondyloarthropathies: Beyond The ‘Classicalmentioning
confidence: 99%